PENGARUH BLENDED LEARNING BERBANTUAN LAB. VIRTUAL PhET DAN GOOGLE CLASSROOM TERHADAP HASIL BELAJAR FISIKA PADA SISWA KELAS X SMA NEGERI 1 TORUE KAB. PARIGI MOUTONG - Artawan, I Made Doni; Syamsu, Syamsu (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2022)
This research aims to determine the effect of  blended learning assisted by the lab. virtual PhET and the google classroom online platform on physics learning outcomes in 10th grader of SMA Negeri 1 Torue in Kab. Parigi Moutong. The type of research conducted is a quasi-experimental design with "Non-Equivalent Control Group Design '' with an experimental class (X MIPA 3) and control (X MIPA 4) selected by purposive sampling technique. The instrument used in this research was a test of learning outcomes in the form of multiple choice. The results of the data processing mean score from the experimental class students' physics learning outcomes was 16.69 from 20 ideal scores with a standard deviation of 2.93. For The control class, the mean score of physical learning outcomes was 12.25 from 20 ideal scores with a standard deviation of 2.86. The hypothesis test was carried out using a two-tailed t-test with a significant level of 5% to obtain the results and. This shows that is in the rejection area. Able to be concluded there is an effect of blended learning assisted by the lab. virtual PhET and the google classroom online platform on physics learning outcomes in 10th graders of SMA Negeri 1 Torue in Kab. Parigi Moutong